What makes you think you are conscious? An agnosticist manifesto - van Leeuwen, Cees (Frontiers in Human Neuroscience, 2015)
The qualitative character of consciousness, its “what-it-is-likeness”, is a contested issue, both in philosophy and psychology. I argue that, rather than by conceptual analyses, the status of “what-it-is-likeness” has to be decided by empirical investigation. Pending the outcome, we should maintain an agnostic stance, in order to remove the bias in favor of fictionalism from our study of consciousness,. I illustrate this with the notion of “ownership unity”. People adhere to the belief of a single, unified self as the owner of their experiences, in spite of abundant dis-unities in the informational content of their experience. On one reading, this supports the notion that the unity of experience is no more than a convenient fiction, based on an illusory experience of unity. Cognitive neuroscience is slanted in favor of such understanding, insofar it emphasizes functional specialization and localization. To restore the balance, I present a complementary perspective: the view that the experience of unity is afforded by the intrinsic, multiscale brain dynamics. This approach offers a biological substrate for unity of experience as a regular scenario within certain boundary conditions, as well mechanisms that may let it go astray.